Development of Microbiology Module “Antibacterial Effect of Ginger Rhizome Extract to Inhibit the Growth of Propionibacterium acnes Bacteria” as a Teaching Material to Improve Students’ Problem Solving Skill - Mahesti, Tika; Hastuti, Utami Sri; Sari, Murni Sapta (BIOEDUKASI, 2024)
This research is a research and development of module on the topic "Antibacterial Effect of Ginger Rhizome Extract to Inhibit the Growth of P. acnes Bacteria" as a teaching material in the learning process to improve students' problem solving skills. The aim of developing the module is to produce a valid, practical and effective teaching materials. The development of module used ADDIE model. Validation of the Microbiology Module was conducted by Microbiology material expert, learning media and teaching material experts, and Microbiology learning practitioner expert. The effectiveness of Microbiology Module in improving problem solving skills can be known through pretest and posttest scores analyzed through One Way Ancova test. The research and development results show that validation scores by learning media and teaching materials experts were 99.72%, Microbiology material experts were 87.56%, biology education practitioner experts were 99.33%, student practical response results were 87.05%. The efficiency results were 0.00 < 0.05 so it proved that the use of module is effective in the learning process, it can be concluded that the Microbiology Module category as very valid, very practical and effective as teaching material, so it can be used by students in Microbiology courses especially in improving problem solving skills.